A growing light in the lagging region in indonesia: The impact of village fund on rural economic growth - Nurlatifah Hartojo; Mohamad Ikhsan; Teguh Dartanto; Sudarno Sumarto (Economies, 2022)
Narrowing the development gap has long been and continues to be a key element of government aspiration worldwide. Since 2015, the Government of Indonesia has implemented the village fund (VF) transfer to enhance its rural economy, especially in remote areas. The impact of the VF on village development may vary greatly depending on the village's location. This study examines the causal effects of VF transfer on the rural economic growth of underdeveloped villages in Indonesia. Using a nighttime light dataset at the village level as a proxy for rural economic growth and a regression discontinuity design in time, we found a significant improvement in rural economic growth in underdeveloped villages after the implementation of VF transfer. Our study confirms that the underdeveloped villages in East Indonesia are growing faster than those in West and Central Indonesia. The average growth of nightlight after the implementation of VF is approximately 156% in East Indonesia, 141% in Central Indonesia, and 98% in West Indonesia compared to the growth of pre-VF. Therefore, there is a strong argument to review the current formula of the VF to narrow the rural development gap in Indonesia.
Keywords: D63; P25; R11; R12; 330; impact evaluation; intergovernmental transfer; regression discontinuity design; remote sensing application; rural development; sustainable development